1996
DOI: 10.1063/1.116635
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency optical response in epitaxial thin films of La0.67Ca0.33MnO3 exhibiting colossal magnetoresistance

Abstract: We report measurements of the low-frequency optical response in epitaxial thin films of La0.67Ca0.33MnO3 in the temperature range covering both the ferromagnetic metallic state and the paramagnetic insulating state. We observe a bolometric optical response in fully oxygenated films of the above composition as well as in oxygen deficient films. In both types of samples, the optical response is thermal in nature as indicated by its proportionality with the temperature derivative of the resistance dR/dT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(41 citation statements)
references
References 4 publications
2
39
0
Order By: Relevance
“…[33][34][35][36] Technological interest has centered on solar cells, light-emitting diodes, and photoelectric detectors. [37,38] Previous researches showed that these materials represent good properties, such as ultrafast response, high-sensitivity, broad-spectrum and position-sensitivity, as optoelectronic device materials.…”
Section: Ultrafast Photoresponse In Oxide Filmsmentioning
confidence: 99%
“…[33][34][35][36] Technological interest has centered on solar cells, light-emitting diodes, and photoelectric detectors. [37,38] Previous researches showed that these materials represent good properties, such as ultrafast response, high-sensitivity, broad-spectrum and position-sensitivity, as optoelectronic device materials.…”
Section: Ultrafast Photoresponse In Oxide Filmsmentioning
confidence: 99%
“…These CMR manganites have the general composition (RE) x (EA) 1-x MnO 3 , where RE is a rare-earth and EA an earthalkaline element. The choice of elements and their ratio x determines the temperature of the metal-insulator transition, and it can be varied over a wide range by adjusting the material composition [6,7]. For low temperature bolometers Nd x Sr (1-x) MnO 3 (NSMO) is appropriate [6], with the transition temperature decreasing with increasing Nd-fraction x. Sensitivities, typically defined through the temperature coefficient of resistance TCR ≡ 1/R × ∂R/∂T, can be around 10%/K, and square resistances for NSMO vary between ~10 and 1000 Ω for film thicknesses from ~20 to 500 nm.…”
Section: A Design Considerationsmentioning
confidence: 99%
“…A bolometric response on the manganite film structures has been investigated recently [7,8]. An experience of the optimization of heat and electrical characteristics of film HTSC bolometers [2] has not been still realized in La -Mn structures.…”
Section: (Received July 22 1999; Revised Version December 10' 1999)mentioning
confidence: 99%